Pt-Sn bimetallic catalyst and preparation method and application thereof
By loading Sn and Pt onto Y molecular sieves to form a Pt-Sn bimetallic catalyst, the problem of high cost of Pt-based catalysts is solved, and a highly efficient catalytic effect is achieved for alkane aromatization reactions.
Patent Information
- Application Number
- CN202511041704.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-11-18
AI Technical Summary
Existing Pt-based catalysts have high production costs due to the high price of the precious metal Pt, and their catalytic performance in alkane aromatization reactions needs to be improved.
Atomic layer deposition (ALD) technology was used to load Sn and Pt onto Y molecular sieves to form a Pt-Sn bimetallic catalyst. The catalytic performance was improved by adjusting the spatial distribution and electronic state of Pt and Sn.
This reduces the production cost of the catalyst and improves the catalytic activity and aromatic selectivity of the alkane aromatization reaction.
Smart Images

Figure BDA0005520583900000081 
Figure BDA0005520583900000091
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of catalyst technology in coal / petroleum chemical industry, and particularly relates to a Pt-Sn bimetallic catalyst and a preparation method and application thereof. BACKGROUND
[0002] Light aromatic hydrocarbons (benzene, toluene, ethylbenzene and xylene) are important basic chemical raw materials, which provide important guarantee for high-quality national living standards. At present, aromatic hydrocarbons are mainly derived from catalytic reforming of naphtha components in crude oil, but the energy structure of rich coal, less oil and lack of gas in China seriously affects the production capacity of aromatic hydrocarbons. The Fischer-Tropsch naphtha prepared by coal indirect liquefaction using syngas as raw material contains a large amount of straight-chain alkanes with low octane number, and it is of great significance to broaden the production capacity of aromatic hydrocarbons and optimize the product structure of Fischer-Tropsch naphtha by converting them into aromatic hydrocarbons through alkanes aromatization technology.
[0003] Pt-based catalysts have attracted much attention in alkanes aromatization reaction due to their strong C-H bond activation ability and weak C-C bond breaking ability. However, Pt is a noble metal, which is relatively expensive, resulting in a significant increase in catalyst production costs. Patent CN 116713028 A shows that the addition of Sn as an additive can improve the dispersion of Pt species, increase the atomic utilization rate of Pt, and thus reduce production costs. Yan et al. (Catal. Sci. Technol., 2023, 13, 1677) showed that the additive Sn can adjust the electronic state of Pt species, and part of the electrons are transferred from Pt to Sn, resulting in the formation of part of the electron-deficient Pt species. The synergistic effect of electron-deficient and electron-rich Pt species effectively improves the octane aromatization performance of the catalyst. SUMMARY
[0004] Therefore, the purpose of the present application is to provide a Pt-Sn bimetallic catalyst and a preparation method and application thereof. The catalyst introduces Sn, which can effectively reduce the production cost of the catalyst, and also adjust the metallic properties of Pt species to improve the catalytic performance.
[0005] The present application provides a preparation method of a Pt-Sn bimetallic catalyst, comprising the following steps:
[0006] 1) Put Y zeolite into a mixed solution of KOH and methanol, stir, centrifuge, wash to neutral, dry, and calcine to obtain non-acidic KY zeolite; the silicon-aluminum ratio of the Y zeolite is 3-100;
[0007] 2) Using the non-acidic KY zeolite as a carrier, Sn is loaded by atomic layer deposition technology to obtain Sn-modified non-acidic KY zeolite;
[0008] 3) taking the Sn-modified non-acidic KY molecular sieve as a carrier, loading Pt by using an atomic layer deposition technology to obtain a Pt-Sn bimetallic catalyst.
[0009] Preferably, the temperature for drying in step 1) is 75-85℃, and the time for drying is 7-9h.
[0010] The temperature for calcination is 440-460℃, and the time for calcination is 170-190min.
[0011] Preferably, the loading of Sn by using an atomic layer deposition technology in step 2) comprises:
[0012] The cycle number of atomic layer deposition of Sn is at least 1, and each cycle comprises: pulse, diffusion and purge of methanol; pulse, diffusion and purge of a Sn source; pulse, diffusion and purge of H2O;
[0013] The time for pulse, diffusion and purge of methanol is respectively 0-5s, 0.5-3s and 90-120s; the time for pulse, diffusion and purge of the Sn source is respectively 0.3-1s, 50-100s and 120-240s; the time for pulse, diffusion and purge of H2O is respectively 0.5-5s, 50-100s and 60-120s.
[0014] The Sn source is selected from one or more of tetrakis(dimethylamino)tin(IV), acetylacetonatostannane and tetraethenyltin.
[0015] Preferably, the loading of Pt by using an atomic layer deposition technology in step 3) comprises:
[0016] The cycle number of atomic layer deposition of Pt is at least 1, and each cycle comprises: pulse, diffusion and purge of methanol; pulse, diffusion and purge of a Pt source; pulse, diffusion and purge of O3;
[0017] The time for pulse, diffusion and purge of methanol is respectively 0.5-3s, 0.5-3s and 90-120s; the time for pulse, diffusion and purge of the Pt source is respectively 0.3-0.6s, 50-90s and 60-180s; the time for pulse, diffusion and purge of O3 is respectively 0.5-5s, 50-100s and 60-120s.
[0018] The Pt source is selected from (trimethyl)methylcyclopentadienyl platinum or / and acetylacetonatoplatinum.
[0019] Preferably, the mass content of Pt in the Pt-Sn bimetallic catalyst in step 3) is 0.1%-0.35%.
[0020] The application provides a Pt-Sn bimetallic catalyst prepared by the preparation method.
[0021] The application provides application of the Pt-Sn bimetallic catalyst prepared by the preparation method in linear alkane aromatization.
[0022] Preferably, the reaction conditions of the linear alkane aromatization are as follows: the reaction temperature is 350-550 DEG C, the reaction pressure is 0.1-0.5 MPa, the mass space velocity is 0.3-1.5 h-1, the molar ratio of H2 to linear alkane is 5:1-10:1. -1
[0023] The application provides a preparation method of a Pt-Sn bimetallic catalyst, which comprises the following steps: 1) placing Y molecular sieve in a mixed solution of KOH and methanol, stirring, centrifuging, washing to neutral, drying and calcining to obtain non-acidic KY molecular sieve; the silicon-aluminum ratio of the Y molecular sieve is 3-100; 2) loading Sn on the non-acidic KY molecular sieve by using atomic layer deposition technology to obtain Sn-modified non-acidic KY molecular sieve; and 3) loading Pt on the Sn-modified non-acidic KY molecular sieve by using atomic layer deposition technology to obtain the Pt-Sn bimetallic catalyst. DETAILED DESCRIPTION
[0024] The application provides a preparation method of a Pt-Sn bimetallic catalyst, which comprises the following steps:
[0025] 1) placing Y molecular sieve in a mixed solution of KOH and methanol, stirring, centrifuging, washing to neutral, drying and calcining to obtain non-acidic KY molecular sieve; the silicon-aluminum ratio of the Y molecular sieve is 3-100;
[0026] 2) loading Sn on the non-acidic KY molecular sieve by using atomic layer deposition technology to obtain Sn-modified non-acidic KY molecular sieve;
[0027] 3) loading Pt on the Sn-modified non-acidic KY molecular sieve by using atomic layer deposition technology to obtain the Pt-Sn bimetallic catalyst.
[0028] The application precisely regulates the spatial distribution of Pt and Sn by using atomic layer deposition technology, and further adjusts the distance between Pt and Sn in the catalyst. The addition of Sn can induce the formation of part of electron-deficient Pt species, promote the dehydrogenation of alkane to olefin, and thus improve the catalytic activity of alkane aromatization and the selectivity of aromatic hydrocarbon.
[0029] The Y molecular sieve is placed in a mixed solution of KOH and methanol, stirred, centrifuged, washed to neutral, dried, and calcined to obtain the non-acidic KY molecular sieve.
[0030] In the present application, the Y molecular sieve has a silicon-aluminum ratio of 3-100; specifically, the silicon-aluminum ratio can be 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100.
[0031] In the present application, the solid-liquid ratio of the Y molecular sieve and methanol is 1:10-1:50; specifically, the solid-liquid ratio can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, or 1:50. The concentration of KOH in the mixed solution of KOH and methanol in the present application is 0.01-0.2 mol / L. The present application adjusts the K content of the Y molecular sieve after K modification by controlling the above-mentioned concentration.
[0032] In the present application, the stirring temperature is room temperature, preferably 10-30℃; the stirring time is 8-30 min. In the present application, the drying temperature is preferably 75-85℃, specifically, the drying temperature can be 75℃, 80℃, or 85℃; the drying time is 7-9 h, specifically, the drying time can be 7 h, 8 h, or 9 h. The calcination temperature is preferably 440-460℃, specifically, the calcination temperature can be 440℃, 445℃, 450℃, 455℃, or 460℃; the calcination time is 170-190 min, specifically, the calcination time can be 170 min, 175 min, 180 min, 185 min, or 190 min.
[0033] After obtaining the non-acidic KY molecular sieve, the present application uses the non-acidic KY molecular sieve as a carrier to load Sn by atomic layer deposition technology to obtain a Sn-modified non-acidic KY molecular sieve.
[0034] The present application uses the atomic layer deposition technology to load Sn, which includes:
[0035] The atomic layer deposition of Sn is performed at least once, and each cycle includes: pulse, diffusion, and purge of methanol; pulse, diffusion, and purge of a Sn source; pulse, diffusion, and purge of H2O;
[0036] The pulse, diffusion and purge time of the methanol are respectively 0-5s, 0.5-3s, 90-120s; the pulse, diffusion and purge time of the Sn source are respectively 0.3-1s, 50-100s, 120-240s; the pulse, diffusion and purge time of the H2O are respectively 0.5-5s, 50-100s, 60-120s. In specific embodiments, the pulse, diffusion and purge time of the methanol are respectively 0.1s, 1s and 90s; the pulse, diffusion and purge time of the Sn source are respectively 0.5s, 90s and 120s; the pulse, diffusion and purge time of the H2O are respectively 1s, 60s and 90s. Or the pulse, diffusion and purge time of the methanol are respectively 3s, 2s and 105s; the pulse, diffusion and purge time of the Sn source are respectively 0.8s, 70s and 180s; the pulse, diffusion and purge time of the H2O are respectively 3s, 80s and 60s. Or the pulse, diffusion and purge time of the methanol are respectively 5s, 3s and 120s; the pulse, diffusion and purge time of the Sn source are respectively 1s, 100s and 240s; the pulse, diffusion and purge time of the H2O are respectively 5s, 100s and 120s.
[0037] In the present application, the Sn source is selected from one or more of tetrakis(dimethylamino)tin(IV), acetylacetone tin and tetra-vinyl tin. In the present application, the deposition temperature of the Sn source is 100-200℃, and can be specifically 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 60℃, 70℃, 180℃, 190℃ or 200℃; the deposition cycle number is 1-5, and can be specifically 1, 2, 3, 4 or 5.
[0038] After obtaining the Sn-modified non-acidic KY molecular sieve, the present application uses atomic layer deposition technology to load Pt on the Sn-modified non-acidic KY molecular sieve, to obtain a Pt-Sn bimetallic catalyst.
[0039] The atomic layer deposition technology used to load Pt in the present application includes:
[0040] The cycle number of the atomic layer deposition of Pt is at least 1, and each cycle includes: pulse, diffusion and purge of methanol; pulse, diffusion and purge of a Pt source; pulse, diffusion and purge of O3;
[0041] The pulse, diffusion and purging time of the methanol are respectively 0.5-3s, 0.5-3s and 90-120s; the pulse, diffusion and purging time of the Pt source are respectively 0.3-0.6s, 50-90s and 60-180s; the pulse, diffusion and purging time of the O3 are respectively 0.5-5s, 50-100s and 60-120s. In specific embodiments, the pulse, diffusion and purging time of the methanol are respectively 0.1s, 1s and 90s; the pulse, diffusion and purging time of the Pt source are respectively 0.5s, 60s and 90s; the pulse, diffusion and purging time of the O3 are respectively 1s, 60s and 90s. Or the pulse, diffusion and purging time of the methanol are respectively 1.5s, 2s and 100s; the pulse, diffusion and purging time of the Pt source are respectively 0.5s, 80s and 150s; the pulse, diffusion and purging time of the O3 are respectively 3s, 80s and 100s. Or the pulse, diffusion and purging time of the methanol are respectively 3s, 3s and 120s; the pulse, diffusion and purging time of the Pt source are respectively 0.6s, 90s and 180s; the pulse, diffusion and purging time of the O3 are respectively 5s, 100s and 120s.
[0042] In the present application, the Pt source is selected from (trimethyl)methylcyclopentadienyl platinum or / and platinum acetylacetonate. The temperature for depositing the Pt source is 150-250℃, and can be specifically 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃ or 250℃; the number of deposition cycles is 1-8, and can be specifically 1, 2, 3, 4, 5, 6, 7 or 8.
[0043] In the present application, in the atomic layer deposition, the methanol can modify the -OH on the surface of the Sn-modified non-acidic KY molecular sieve into -OCH3, and neither the Sn source nor the Pt source can be adsorbed at the -OCH3 site. Based on this, by adjusting whether there is a methanol pulse before the Pt / Sn deposition and the pulse time of the methanol, the number of active sites on the outer surface of the carrier can be changed, and then the distance between Pt and Sn can be adjusted. For example, if methanol pre-adsorption is performed before Sn deposition, the pulsed methanol will preferentially occupy the adsorption sites on the outer surface of the molecular sieve, so that Sn can only be deposited in the pore channel of the molecular sieve, and the methanol pre-adsorption before Pt deposition makes Pt diffuse into the pore channel and fall into position, and then the distance between Pt and Sn is relatively short; on the contrary, if the methanol does not preferentially occupy before Sn deposition, it is more likely to be located on the outer surface of the molecular sieve, and the methanol pre-adsorption before Pt deposition will cause Pt to diffuse into the pore channel, and then Pt is inside and Sn is outside, so as to realize the adjustment of the distance between Pt and Sn.
[0044] The mass content of Pt in the Pt-Sn bimetallic catalyst prepared by the method is 0.1% to 0.35%; and the specific content is 0.1%, 0.15%, 0.2%, 0.25%, 0.30% or 0.35%.
[0045] The application provides a Pt-Sn bimetallic catalyst prepared by the method.
[0046] The application provides an application of the Pt-Sn bimetallic catalyst prepared by the method in straight-chain alkane aromatization.
[0047] In the application, the straight-chain alkane is C6 to C 10 , preferably n-octane; and the aromatization product is preferably C8 aromatic hydrocarbon.
[0048] In the application, the reaction conditions of the straight-chain alkane aromatization are as follows: the reaction temperature is 350 to 550 DEG C, and specifically can be 350 DEG C, 360 DEG C, 370 DEG C, 380 DEG C, 390 DEG C, 400 DEG C, 410 DEG C, 420 DEG C, 430 DEG C, 440 DEG C, 450 DEG C, 460 DEG C, 470 DEG C, 480 DEG C, 490 DEG C, 500 DEG C, 510 DEG C, 520 DEG C, 530 DEG C, 540 DEG C or 550 DEG C; the reaction pressure is 0.1 to 0.5 MPa, and specifically can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa or 0.5 MPa; the mass space velocity is 0.3 to 1.5 h -1 , and specifically can be 0.3 h -1 , 0.35 h -1 , 0.4 h -1 , 0.45 h -1 , 0.5 h -1 , 0.55 h -1 , 0.6 h -1 , 0.65 h -1 , 0.7 h -1 , 0.75 h -1 , 0.8 h -1 , 0.85 h -1 , 0.9 h -1 , 1.0 h -1 , 1.05 h -1 , 1.1 h -1 , 1.15 h -1 , 1.2 h -1 , 1.25 h -1 , 1.3 h -1 , 1.35 h -1 , 1.4 h -1 , 1.45 h -1 or 1.5 h -1; the molar ratio of H2 and straight-chain alkane is 5:1-10:1, and can be 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0049] In order to further illustrate the present application, a Pt-Sn bimetallic catalyst, a preparation method and application thereof provided by the present application are described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the present application.
[0050] Example 1
[0051] 1. 1.5 g of Y molecular sieve with a silicon-aluminum ratio of 25 was weighed into 0.17 g of KOH and 60 mL of methanol, stirred at room temperature for 10 min, then centrifuged and washed to neutral. Subsequently, it was dried at 75°C for 9 h and calcined at 440°C for 190 min to obtain a non-acidic KY molecular sieve.
[0052] 2. The non-acidic KY molecular sieve prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, dried at room temperature, and then placed in an ALD cavity for Sn loading. The reaction cavity temperature was controlled at 150°C, the N2 flow rate was 50 mL / min, and the deposition cycle number was 2. The methanol use temperature was room temperature, and the pulse, diffusion and purge times were 0.1 s, 1 s and 90 s, respectively; the use temperature of tetra(dimethylamino)tin (Sn source molecule) was 65°C, and the pulse, diffusion and purge times were 0.5 s, 90 s and 120 s, respectively; the pulse, diffusion and purge times of H2O were 1 s, 60 s and 90 s, respectively, to obtain a Sn-modified non-acidic KY molecular sieve.
[0053] 3. The Sn-modified non-acidic KY molecular sieve prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, dried at room temperature, and then placed in an ALD cavity for Pt loading. The reaction cavity temperature was controlled at 200°C, the N2 flow rate was 150 mL / min, and the deposition cycle number was 3. The methanol use temperature was room temperature, and the pulse, diffusion and purge times were 0.1 s, 1 s and 90 s, respectively; the use temperature of (trimethyl)methylcyclopentadienyl platinum (Pt source molecule) was 60°C, and the pulse, diffusion and purge times were 0.5 s, 60 s and 90 s, respectively; the pulse, diffusion and purge times of O3 were 1 s, 60 s and 90 s, respectively, to obtain a Pt-Sn bimetallic catalyst.
[0054] Example 2:
[0055] 1. 1.5 g of Y molecular sieve with a silicon-aluminum ratio of 25 was weighed into 0.17 g of KOH and 60 mL of methanol, stirred at room temperature for 20 min, then centrifuged and washed to neutral. Subsequently, it was dried at 80°C for 8 h and calcined at 450°C for 180 min to obtain a non-acidic KY molecular sieve.
[0056] 2. The non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and placed in an ALD chamber for Sn loading. The reaction chamber temperature was controlled at 150 °C, the N2 flow rate was 50 mL / min, and the deposition cycle number was 2. The methanol temperature was room temperature, and its pulse, diffusion, and purge times were 3 s, 2 s, and 105 s, respectively; the acetylacetone tin (Sn source molecule) temperature was 70 °C, and its pulse, diffusion, and purge times were 0.8 s, 70 s, and 180 s, respectively; the H2O pulse, diffusion, and purge times were 3 s, 80 s, and 60 s, respectively, to obtain Sn-modified non-acidic KY zeolite.
[0057] 3. The Sn-modified non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and placed in an ALD chamber for Pt loading. The reaction chamber temperature was controlled at 200 °C, the N2 flow rate was 150 mL / min, and the deposition cycle number was 3. The methanol temperature was room temperature, and its pulse, diffusion, and purge times were 1.5 s, 2 s, and 100 s, respectively; the acetylacetone platinum (Pt source molecule) temperature was 80 °C, and its pulse, diffusion, and purge times were 0.5 s, 80 s, and 150 s, respectively; the O3 pulse, diffusion, and purge times were 3 s, 80 s, and 100 s, respectively, to obtain a Pt-Sn bimetallic catalyst.
[0058] Example 3
[0059] 1. 1.5 g of Y zeolite with a silicon-aluminum ratio of 25 was weighed into 0.17 g of KOH and 60 mL of methanol, stirred at room temperature for 30 min, and then centrifuged and washed to neutral. Subsequently, it was dried at 85 °C for 7 h and calcined at 460 °C for 170 min to obtain a non-acidic KY zeolite.
[0060] 2. The non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and placed in an ALD chamber for Sn loading. The reaction chamber temperature was controlled at 150 °C, the N2 flow rate was 50 mL / min, and the deposition cycle number was 2. The methanol temperature was room temperature, and its pulse, diffusion, and purge times were 5 s, 3 s, and 120 s, respectively; the tetraethenyl tin (Sn source molecule) temperature was 65 °C, and its pulse, diffusion, and purge times were 1 s, 100 s, and 240 s, respectively; the H2O pulse, diffusion, and purge times were 5 s, 100 s, and 120 s, respectively, to obtain Sn-modified non-acidic KY zeolite.
[0061] 3. The Sn-modified non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and then placed in an ALD cavity for Pt loading. The reaction cavity temperature was controlled at 200 °C, the N2 flow rate was 150 mL / min, and the deposition cycle number was 3. The methanol usage temperature was room temperature, and its pulse, diffusion, and purge times were 3 s, 3 s, and 120 s, respectively; the (trimethyl)methylcyclopentadienyl platinum (Pt source molecule) usage temperature was 60 °C, and its pulse, diffusion, and purge times were 0.6 s, 90 s, and 180 s, respectively; the pulse, diffusion, and purge times of O3 were 5 s, 100 s, and 120 s, respectively, to obtain a Pt-Sn bimetallic catalyst.
[0062] Comparative Example
[0063] 1. 1.5 g of Y zeolite with a silicon-aluminum ratio of 25 was weighed into 0.17 g of KOH and 60 mL of methanol, stirred at room temperature for 10 min, and then centrifuged and washed to neutral. Subsequently, it was dried at 80 °C for 8 h and calcined at 450 °C for 180 min to obtain a non-acidic KY zeolite.
[0064] 2. The non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and then placed in an ALD cavity for Sn loading. The reaction cavity temperature was controlled at 150 °C, the N2 flow rate was 50 mL / min, and the deposition cycle number was 2. The tetrakis(dimethylamino)tin (Sn source molecule) usage temperature was 65 °C, and its pulse, diffusion, and purge times were 0.5 s, 90 s, and 120 s, respectively; the pulse, diffusion, and purge times of O3 were 1 s, 60 s, and 90 s, respectively, to obtain a Sn-modified non-acidic KY zeolite.
[0065] 3. The Sn-modified non-acidic KY zeolite prepared above was ground and dispersed in ethanol, and uniformly coated on a quartz sheet, which was dried at room temperature and then placed in an ALD cavity for Pt loading. The reaction cavity temperature was controlled at 200 °C, the N2 flow rate was 150 mL / min, and the deposition cycle number was 3. The methanol usage temperature was room temperature, and its pulse, diffusion, and purge times were 1 s, 1 s, and 90 s, respectively; the (trimethyl)methylcyclopentadienyl platinum (Pt source molecule) usage temperature was 60 °C, and its pulse, diffusion, and purge times were 0.5 s, 60 s, and 90 s, respectively; the pulse, diffusion, and purge times of O3 were 1 s, 60 s, and 90 s, respectively, to obtain a Pt-Sn bimetallic catalyst.
[0066] Test Example
[0067] The prepared catalysts were evaluated for aromatization performance using n-octane as a model reactant. 0.5 g of the prepared Pt-Sn bimetallic catalyst was mixed with quartz sand and loaded into a fixed bed reactor tube, which was reduced at 500℃ for 1 h under a H2 flow rate of 50 mL / min. After reduction, the temperature of the reactor tube was lowered to the reaction temperature, and the H2 flow rate was adjusted to 8 mL / min. Subsequently, the liquid pump was turned on, and the liquid flow rate was 0.8 mL / h. The products (online reaction for 10 h) were analyzed by online gas chromatography after being heated at 200℃, and the details are shown in Table 1:
[0068] Table 1 Evaluation results of the catalytic performance of the catalysts in the examples and comparative examples
[0069]
[0070]
[0071] As can be seen from the above examples, the present application provides a preparation method of a Pt-Sn bimetallic catalyst, which comprises the following steps: 1) placing Y molecular sieve in a mixed solution of KOH and methanol, stirring, centrifuging, washing to neutral, drying, and calcining to obtain non-acidic KY molecular sieve; the Si / Al ratio of the Y molecular sieve is 3-100; 2) using the non-acidic KY molecular sieve as a carrier, loading Sn by atomic layer deposition technology to obtain Sn-modified non-acidic KY molecular sieve; 3) using the Sn-modified non-acidic KY molecular sieve as a carrier, loading Pt by atomic layer deposition technology to obtain a Pt-Sn bimetallic catalyst. The preparation method provided by the present application combines atomic layer deposition technology to precisely control the spatial distribution of Pt and Sn, thereby adjusting the electronic state of Pt species, promoting the dehydrogenation of alkanes to olefin intermediates, and improving the catalytic activity of alkanes and the selectivity of aromatic hydrocarbons.
[0072] The above only describes the preferred embodiments of the present application, and it should be noted that those skilled in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered within the protection scope of the present application.
Claims
1. A method for preparing a Pt-Sn bimetallic catalyst, comprising the following steps: 1) Place the Y molecular sieve in a mixture of KOH and methanol, stir, centrifuge, wash until neutral, dry, and calcine to obtain a non-acidic KY molecular sieve; the silica-to-alumina ratio of the Y molecular sieve is 3-100. 2) Using the aforementioned non-acidic KY molecular sieve as a support, Sn is loaded onto it using atomic layer deposition technology to obtain Sn-modified non-acidic KY molecular sieve; 3) Using the Sn-modified non-acidic KY molecular sieve as a support, Pt is loaded using atomic layer deposition technology to obtain a Pt-Sn bimetallic catalyst.
2. The preparation method according to claim 1, characterized in that, The drying temperature is 75–85°C, and the drying time is 7–9 hours. The roasting temperature is 440–460℃, and the roasting time is 170–190 min.
3. The preparation method according to claim 1, characterized in that, The Sn loading using atomic layer deposition technology includes: The atomic layer deposition of Sn is performed at least once, and each cycle includes: pulse, diffusion and purging of methanol; pulse, diffusion and purging of the Sn source; pulse, diffusion and purging of H2O; The pulse, diffusion, and purging times for the methanol are 0–5 s, 0.5–3 s, and 90–120 s, respectively; the pulse, diffusion, and purging times for the Sn source are 0.3–1 s, 50–100 s, and 120–240 s, respectively; and the pulse, diffusion, and purging times for H2O are 0.5–5 s, 50–100 s, and 60–120 s, respectively.
4. The preparation method according to claim 1, characterized in that, The Pt loading using atomic layer deposition technology includes: The atomic layer deposition of Pt is performed in at least one cycle, each cycle including: pulse, diffusion and purging of methanol; pulse, diffusion and purging of the Pt source; pulse, diffusion and purging of O3; The pulse, diffusion, and purging times for the methanol are 0.5–3 s, 0.5–3 s, and 90–120 s, respectively; the pulse, diffusion, and purging times for the Pt source are 0.3–0.6 s, 50–90 s, and 60–180 s, respectively; and the pulse, diffusion, and purging times for the O3 source are 0.5–5 s, 50–100 s, and 60–120 s, respectively.
5. The preparation method according to claim 3, characterized in that, The Sn source is selected from one or more of tetra(dimethylamino)tin(IV), tin acetylacetonate, and tetravinyltin.
6. The preparation method according to claim 4, characterized in that, The Pt source is selected from (trimethyl)methylcyclopentadienyl platinum or / and acetylacetonate platinum.
7. The preparation method according to claim 1, characterized in that, The Pt content in the Pt-Sn bimetallic catalyst is 0.1% to 0.35% by mass.
8. A Pt-Sn bimetallic catalyst, prepared by the method described in any one of claims 1 to 7.
9. The application of a Pt-Sn bimetallic catalyst prepared by the method according to any one of claims 1 to 7 in the aromatization of straight-chain alkane.
10. The application according to claim 9, characterized in that, The reaction conditions for the aromatization of straight-chain alkanes are: reaction temperature of 350–550℃, reaction pressure of 0.1–0.5 MPa, and mass hourly space velocity of 0.3–1.5 h⁻¹. -1 The molar ratio of H2 to straight-chain alkanes is 5:1 to 10:1.
Citation Information
Patent Citations
Catalyst based on Sn modified KL molecular sieve as well as preparation method and application of catalyst
CN116713028A
Cited By
High-efficiency stable Pt-based catalyst for dehydrogenation of n-octane and preparation method of high-efficiency stable Pt-based catalyst
CN121797308A
A non-noble metal dehydrogenation catalyst for n-octane dehydrogenation and a preparation method thereof
CN122644049A